Upaya Meningkatkan Karakter Religius Guru dan Siswa Melalui Program Tahfidz Al-Quran di MIN 3 Banyumas - Rizki Fitrianto; Sabar Munanto (Medan Resource Center, 2022)
Increasing Islamic values ??in madrasas is highly dependent on several factors. A very important factor, among others, is the application of religious culture towards quality improvement. Values ??Religious character is a positive thing that must be maintained and implemented by all school members without feeling forced. One of the values ??of religious character that must be maintained is implementing the Al-Qura’an in everyday life, including teachers and students in memorizing the Al-Qur’an. method.In this School Action Research (PTS), an action was tried in the form of implementing the TAHFIDZ AL-QURAN PROGRAM for teachers and students at MI Negeri 3 Banyumas.This research was carried out in two cycles, because from the results of research and data analysis, it turned out that in the second cycle, the values ??of the religious character of teachers and students in the Tahfidz Al-Quran learning process increased and met the predetermined indicators of 75%. From the results of this study, it can be concluded that to increase the religious values ??of teachers and students can be done by implementing the Tahfidz Al-Quran Program.